Implementasi Kebijakan Insentif Pajak Penghasilan Final Bagi Pelaku Usaha Mikro Kecil Dan Menengah (UMKM) Pada Masa Pandemi Covid 19 Di KPP Pratama Bekasi Utara Tahun 2019-2021 - Linda Puji Lestari; Mainita Hidayati (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The phenomenon of this study was that there were still many MSMEs that have not utilized and could not take advantage of incentive policy as they did not know the mechanism in detail. Moreover, the realization report mechanism which was too complicated made the incentive policy could not be implemented properly. The objective of this study were to find out the implementation of the incentive policy of final income tax (PPH) for MSMEs during the Covid-19 pandemic at KPP Pratama North Bekasi in 2019-2021, as well as the obstacles and effort faced in implementing this policy. The data were analyzed by employing a qualitative method. The results of this study showed that the implementation of the incentive policy of the final PPH has not gone well. It could be seen by the existence of several indicators based on George Edward III's theory, namely the lack of optimal socialization from each region in providing education about the use of the incentive policy of the final PPH, low awareness, taxpayers’ compliance, the taxpayers attitude who was still clueless in online realization reports through the DGT Online website. In addition, this could also be seen based on the data on the the number of taxpayers reporting MSME DTP Tax Incentives in 2020 as many as 598 of the totals who submitted applications of 844 with an incentive realization of Rp. 2,705,657,325, and the number of registered MSME taxpayers at KPP Pratama North Bekasi was 3,106.